STRATEGI OPTIMALISASI KLAIM JAMINAN KESEHATAN NASIONAL DI UNIT CASEMIX RUMAH SAKIT “X” BLITAR - Syahira, Nurfathina; Rusdi, Achmad Jaelani; Akbar, Prima Soultoni (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2024)
The funding for patient care of participants of the Social Security Administering Body (BPJS) Health in hospitals is carried out through a claim mechanism. This study aims to design a strategy to optimize the claims for patient care costs for BPJS participants at Hospital "X" in Blitar. The study is conducted with a descriptive qualitative approach, and data collection is done through interviews and Focus Group Discussions (FGD). The informants consist of a doctor and four coders in the casemix unit. The study begins with an analysis of the claim service system situation, focusing on strengths, weaknesses, opportunities, and threats (SWOT). From the collected SWOT, an assessment of alternative strategies is carried out to avoid issues in the claims process, based on the interaction between internal and external elements. The study found that the informants prioritized strategies derived from the strengths and opportunities (SO), including enhancing the integration of the hospital's information system with BPJS, effectively implementing BPJS guidelines in the coding and claim process, and leveraging BPJS responsiveness to expedite claim resolution to improve the speed of the claims process.